Mapping of the C3d receptor (CR2)-binding site and a neoantigenic site in the C3d domain of the third component of complement. - Lambris, J D (1985)
The C3d domain of C3 contains the site that binds to the C3d receptor (CR2) which is expressed on B lymphocytes. It also contains a neoantigenic determinant that is recognized by monoclonal antibody (mAb) 130 and is expressed when C3b is cleaved to iC3b and subsequently to C3dg or C3d. mAb 130 inhibits the binding of C3d to CR2. In this study, the locations of the CR2-binding site and of the neoantigen recognized by mAb 130 within the C3d domain were investigated. Treatment of human C3d with CNBr generated two major fragments with Mrs of 12,500 and 8600. Binding studies showed that only the Mr 8600 fragment was capable of binding to both CR2 and mAb 130. Amino-terminal sequence analysis of the Mr 8600 fragment and comparison with the amino acid sequence derived from human C3 cDNA [de Bruijn, M. H. L. & Fey, G. H. (1985) Proc. Natl. Acad. Sci. USA 82, 708-712] placed it between residues 1199 and 1274 of the C3 sequence. Several peptides were synthesized according to the derived C3 sequence of amino acid residues 1209-1236. Based on their differential binding to CR2 and mAb 130, we localized the CR2-binding site and mAb 130 neoantigenic site, respectively, to residues 1227-1232 and 1217-1232 of the C3 sequence.